Experimentally comparing the attractiveness of domestic lights to insects: Do LEDs attract fewer insects than conventional light types?. Issue 22 (13th October 2016) - Wakefield, Andrew; Broyles, Moth; Stone, Emma L.; Jones, Gareth; Harris, Stephen
Abstract: LED lighting is predicted to constitute 70% of the outdoor and residential lighting markets by 2020. While the use of LEDs promotes energy and cost savings relative to traditional lighting technologies, little is known about the effects these broad‐spectrum "white" lights will have on wildlife, human health, animal welfare, and disease transmission. We conducted field experiments to compare the relative attractiveness of four commercially available "domestic" lights, one traditional (tungsten filament) and three modern (compact fluorescent, "cool‐white" LED and "warm‐white" LED), to aerial insects, particularly Diptera. We found that LEDs attracted significantly fewer insects than other light sources, but found no significant difference in attraction between the "cool‐" and "warm‐white" LEDs. Fewer flies were attracted to LEDs than alternate light sources, including fewer Culicoides midges (Diptera: Ceratopogonidae). Use of LEDs has the potential to mitigate disturbances to wildlife and occurrences of insect‐borne diseases relative to competing lighting technologies. However, we discuss the risks associated with broad‐spectrum lighting and net increases in lighting resulting from reduced costs of LED technology. Abstract : As the LED lighting sector continues to grow globally, we investigated how LED bulbs compare in their attractiveness to nocturnal insects. We found that LEDs attracted significantly fewer insects than other competing light sources, but found no significant difference in attraction between the "cool‐" and "warm‐white" LEDs. Fewer flies were attracted to LEDs than alternate light sources, including fewer biting Culicoides midges (Diptera: Ceratopogonidae).